Hints of the intellectual and philosophical contributions of the female followers (Al-Taba’yat) in the Umayyad period (41 AH – 132 AH / 661 AD – 750 AD) - أسعد عبدالحميد قصي (Al-Adab Journal, 2018)
The contributions of the female followers (Al-Taba’yat) (may Allah be pleased with them) in honor of carrying the Hadith of the Prophet, and their impact on the education of the sciences of the Holy Quran and the Hadith in their educational sessions have resulted in the graduation of scholars and imams of Muslims such as Erwa bin Zubair and Muhammed bin Muslim Al-Zuhri and Abu Bakr Al-Ansari and others. The impact of the codification of the Prophet’s Hadith during the Umayyad period (41 AH / 132 AH / 661 AD - 750 AD) was important in the activity of intellectual and scientific movement in the Islamic community, as a result of the efforts of scholars and jurists of the male and female followers of the Muslims (may Allah be pleased with them) whom made bridges between the study of the Prophet’s Hadith and Islamic history. The teaching classes of the female followers (Al-Taba’yat) were not held only in the mosques, but were held in their houses. They were teaching men and women reading and writing The Holy Qur’an and its explanation, also teaching them the prophetic sayings (AlSunnah) of Messenger Mohammed (Peace be upon him). Furthermore, their effect on collecting the Prophetic sayings (Sunnah), and their effect on the writing of the (Sunnah) on the Umayyad period, therefore, the history write their distinguished intellectual and philosophical in the Islamic sciences.